DIAGNOSTIC MODALITIES AND PHYSICAL THERAPY IN PATIENTS WITH CARPAL TUNNEL SYNDROME - Bulatović, Darko; Nikolić, Dejan (Medicinski podmladak, 2022)
Carpal tunnel syndrome (CTS) represents one of the most common compressive peripheral neuropathies on the upper extremities, and is characterized by compression of the medial nerve on its way through the carpal tunnel area. The first changes experienced by patients with CTS are sensory and occur mainly at night, and if they are not recognized and treated in time, they progress and become continuously present. Prolonged compression of the medial nerve in the region of the carpal tunnel can lead to permanent damage to this nerve, which can result in the patient losing the ability to distinguish between hot and cold, as well as atrophy of the thenar muscles and difficulty in palmar abduction of the thumb. The diagnosis of CTS is generally made based on the patient's symptoms, clinical history and anamnesis, as well as electrodiagnostic tests. In addition to these methods, provocative tests, nuclear magnetic resonance (NMR) and ultrasound examinations are used in the evaluation of CTS. In patients with CTS, a large number of treatment methods, both surgical and non-surgical, are used in clinical practice. Myofascial massage, ultrasound, interference currents, continuous short-wave diathermy, extracorporeal shock wave therapy (ESWT) have been shown to be beneficial in reducing pain and symptoms or improving function in patients with CTS in the short and medium term. It was also pointed out that there are no firm conclusions about optimal doses and therapeutic parameters. A better understanding of the etiology and pathophysiological mechanisms of CTS as well as the effects of certain therapeutic modalities in the treatment of this condition will contribute to further understanding of the origin and progression of CTS as well as the possibilities of prevention and treatment of these patients in order to improve the quality of their life and the functionality of the affected limb.
Keywords: Carpal tunnel syndrome; symptoms; signs; diagnostics; physical therapy